The crystal structure of bepotastine besilate, C27H31ClN2O6S - Wang Fengfeng; Luan Lin; Hu Xiaowen; Zhang Caiyu; Liu Yang (Zeitschrift für Kristallographie - New Crystal Structures)
C27H31ClN2O6S, triclinic, P1 (no. 1), a = 8.0223(3) Å, b = 9.8143(3) Å, c = 10.2307(4) Å, α = 88.308(3)°, β = 69.000(3)°, γ = 65.970(3)°, V = 680.39(5) Å3, Z = 1, R gt(F) = 0.0406, wRref (F 2) = 0.1165, T = 297 K.